Hey can u please help please
austine7361 avatar

Answers

Answer 1
Answer: in a triangular prism, B usually stand for the triangular base of the prism. It is the area of the triangle.

Area of a right triangle = ab/2
a = long leg ; b = short leg

Given measures are:
a = 4 yd ; b = 3 yd

A = (4 yd * 3 yd)/2 = 12 yd² / 2 = 6 yd² is the value of B.

the hypotenuse is 5 yd but it is not needed to get the area of the right triangle base. 7 yd is the measure of the height of the triangular prism.
Answer 2
Answer:

what is B) also.............



Related Questions

Hunter thought he purchased an umbrella for $60. The actual price of an Umbrella is $50. What is hunters percent error
Is 96 fluid ounces greater than less than or equal to 8 pints
Please answer this question
Which is NOT an example of an internal response to stimuli?A. A deer sees a wolf and runs away.B. A bean seedling bends towards the sun.C. A rabbit feels thirsty and drinks water.D. The sun shines over an entire field of sunflowers.
Translate the word phrase into a math expression.  nine more than five times a number                                           A. 9 > 5n B. 9 – 5n    C. 5n – 9                                                  D. 5n + 9

I need to know how to multiply integers.

Answers

An example would be:

4 x 5 = 20

I think its the same way you multiply normal numbers.

What is the expanded form for 6 x 532=

Answers

Answer:

Distributive property is used to find the expanded form.  

Step-by-step explanation:

We are given an expression:

6* 532

This expression can be evaluated with the help of distributive property.

  • It helps to solve complicated multiplication problem easily by splitting the term into addends and then adding each product.
  • a* (b + c) = (a* b) + (a* c)

Working:

6* 532\n=6* (500 + 30 + 2)\n=(6* 500)+(6* 30)+(6* 2)\n=3000 + 180 + 12\n= 3192

3192 = 3000 + 100 + 90 + 2

The expanded form for 6 x 532 is 3,000 + 100 + 90 + 2 (3,192).

X squared minus 36 equals 0. Solve for x

Answers

Answer: x = 6

Step-by-step explanation:

x^2 - 36 = 0

+ 36

x^2 = 36

We know 6^2 = 36

We can conclude that x = 6

6^2 - 36 = 0

36 - 36 = 0

0 = 0

Answer:

x = 6

Step-by-step explanation:

x has to be squared by 6 because 6x6 is 36. Then, you subtract 36 from 36 to get 0. This is how to solve this. I hope it helps.

When doing division and writing down the answer does the "remainder" get put behind a decimal point? (18 POINTS)

Answers

yes 4.5 would be 4 wholes and .5 or 1/2 away from making another whole

Simplify. Show your work.

(x−1)(2x^2+2x+2)

Answers

Here is the answer :)

62 decreased by 37% i would like to know what that is cause i have a test tomorrow and i need help understanding this

Answers

37 \% \ of \ 62 \n\ 37 = .37 \n\
Other Questions